Global plan of action of FAO for animal genetic resources and its application in Latin America and the Caribbean - da Silva, Arthur (Cuban Journal of Agricultural Science, 2014)
This paper has as main objectives to: a) explain the inclusion of the animal genetic resources in the scope of the Commission of Genetic Resources for Food and Agriculture; b) describe the way countries act together with FAO in taking decisions on animal genetic resources; c) submit the strategic priorities of action adopted at the International Technical Conference on Animal Genetic Resources, that took place in Interlaken in 2007; d) give details of the structure of the Network of Animal Genetic Resources of FAO, where the Regional Focal Point of AnGR for Latin America and the Caribbean is included; e) inform on the Financing Strategy, whose first call was in 2012. Key words: conservation, breeds locally adapted, sustainable utilization